Tanfīżu Al-wasā’il As-sam‘iyyah Al-baṣariyyah At-tafā‘uliyyah fī Tanmiyah Mahārah Al-kitābah Al-ibdā‘iyyah Ladā Tālibāt Ma‘had Wali Songo lil-Banāt - Abdullah Syamil Imanuddin; Chusnia Rahmawati (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
This study aims to describe and analyze the implementation of interactive audio-visual media in Arabic language learning to improve the creative writing skills of students in the Arabic Language Program at Ma’had Wali Songo Putri Cukir Jombang. The study employs a qualitative approach with a case study method. Data were collected through in-depth interviews, direct observation, and documentation, involving teachers and students as participants. The findings indicate that the use of interactive audio-visual media, particularly short Arabic-language videos without subtitles, has been effectively implemented and well integrated into the learning process. This media provides authentic language contexts that facilitate students’ comprehension. The learning process is conducted systematically through three stages: introduction, main activities (listening, vocabulary discussion, and idea development), and closing (evaluation and feedback). The implementation of this method contributes to the improvement of students’ creative writing skills, as reflected in the fluency of ideas, vocabulary diversity, and paragraph organization. In addition, students’ motivation and self-confidence also increased. Supporting factors include the attractiveness and variety of the media, students’ enthusiasm, and the teacher’s guidance. However, several challenges were identified, such as limited vocabulary, differences in students’ abilities, and the speed of language in the videos, which can be addressed through appropriate instructional strategies.